ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PT BANK SULUT, TBK DI MANADO - L. M. Mumu, Lenny L. M. Mumu; K. Tungka, Alebert; L. Tampi, Dolina (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. This study is based on that financial performance is a comparison of financial information with ratios that are now with the past and the future on the internal ratio of the banking sector and banking banking finance lain.Kinerja by calculating financial ratios, so that it can be seen the performance ratio analysis such as liquidity, solvency, profitability.This study aimed to compare the performance of a certain period in PT Bank Sulut TBk. Analysis of the research results in the calculation of the financial statements .Bank Sulut period in 2012 and 2013 period.Keywords: financial performance, financial